Analysis of the Effect of Attributes (Safety, Comfort) on 4asc Attributes on Visitor Satisfaction in Tourism Destinations in Samosir Regency - Akbar, Saydillah Isya; Sibarani, Robert; Charloq, Charloq (International Conference on Sciences Development and Technology, 2022)
This study aims to analyze the effect of the safeness and comfort attributes on the 4ASC attribute ( Attractions, Accessibility, Amenities, Ancillary, Safeness, and Comfort) on the satisfaction of visitors to Samosir Regency tourist destinations. Multiple linear regression analysis methods are used to examine the relationship between these attributes with the level of visitor satisfaction. The sampling technique in this study was a non-probability sampling of as many as 135 respondents. Methods of data analysis using multiple regression analysis. The results showed that Safety and Comfort influenced visitor satisfaction. The data collected included the 4ASC attributes, safety, comfort, and visitor satisfaction. The results of the analysis show a significant effect of safety and comfort attributes on visitor satisfaction. The implication of this research is the importance of paying attention to safety and comfort factors in tourism development in Samosir Regency, to increase visitor satisfaction and support tourism growth in the area.